Fantastyczny tygiel. Synkretyzm gatunkowy i kulturowy w cyklu urban fantasy Bena Aaronovitcha „Rzeki Londynu” - Sylwia Borowska-Szerszun (Creatio Fantastica, 2018)
The article A Fantastic Crucible: Genological and Cultural Syncretism in Ben Aaronovitch Urban Fantasy Series “Rivers of London” explores generic and cultural syncretism in the eponymous cycle. Having defined urban fantasy, the author proceeds to place emphasis on the overwhelming heterogeneity adopted within the genre, which suggests its openness to various influences, transformations and modifications. In this particular case the elements of urban fantasy and the criminal novel have been successfully incorporated to create a harmonious whole. Examining the vision of a city of London as a melting pot, Borowska-Szerszun argues that the fantastic level of the text has been construed as just one more component of multicultural London, in which different cultures, nationalities and religions meet. Aaronovitch’s cycle is shown, therefore, as breaking the predominance of whiteness in the fantasy genre, and introducing, instead, social and cultural diversity, which reveals the potential of urban fantasy to deal with difficult issues of our times and provide a valid commentary about contemporary reality.